2017
DOI: 10.1186/s12974-017-0976-5
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin reduces experimental autoimmune encephalomyelitis severity via neuroprotective mechanisms

Abstract: BackgroundTreatment with erythropoietin (Epo) in experimental autoimmune encephalomyelitis (EAE), the rodent model of multiple sclerosis (MS), has consistently been shown to ameliorate disease progression and improve overall outcome. The effect has been attributed to modulation of the immune response and/or preservation of the central nervous system (CNS) tissue integrity. It remains unclear, however, if (a) Epo acts primarily in the CNS or the periphery and if (b) Epo’s beneficial effect in EAE is mainly due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…In addition, there is evidence suggesting that activation of the HIF pathway may be also linked to neuroprotection and perhaps remyelination [ 15 ]. Thus, the erythropoietin (EPO) gene is HIF-dependent, and EPO is neuroprotective in different animal models of MS [ 16 , 17 ]. In addition, methylprednisolone, a widely used glucocorticoid for treating MS, protects oligodendrocytes from excitotoxicity through a HIF-1α-dependent pathway [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is evidence suggesting that activation of the HIF pathway may be also linked to neuroprotection and perhaps remyelination [ 15 ]. Thus, the erythropoietin (EPO) gene is HIF-dependent, and EPO is neuroprotective in different animal models of MS [ 16 , 17 ]. In addition, methylprednisolone, a widely used glucocorticoid for treating MS, protects oligodendrocytes from excitotoxicity through a HIF-1α-dependent pathway [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…We reported previously that EPO secreted by astrocytes is protective for several brain cell types [21][22][23]. In addition, studies involving animal models have shown that EPO in the brain contributes significantly to neuroprotection [24][25][26][27]. Based on these data, we examined the effect of hypothermia on EPO expression in cultured astrocytes.…”
Section: Discussionmentioning
confidence: 98%
“…The neuroprotective properties of erythropoietin have been investigated for a number of years, regarding, for example, stroke and Alzheimer’s disease [67], autoimmune encephalomyelitis [68], neuroprotection in pre-term infants [69], as well as other neurodegenerative and traumatic diseases with cerebral damage such as Parkinson’s disease, traumatic brain injury, and cardiac arrest [70,71]. Kristensen et al’s two studies observed both an endogenous (correlated to baseline RAS activity) and exogenous neuroprotective effect on cognitive function (endogenous) and reaction time (exogenous) [27,28].…”
Section: Discussionmentioning
confidence: 99%